Mengatasi Intoleransi Beragama: Sebuah Tawaran Moderasi Beragama Perspektif Syiah - Dede Syarif (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Abstract Authoritatively promoted in 2019 by the government to counter religious radicalism, the study and implementation of religious moderation has taken more on Sunni viewpoint. Whereas, as a open conceptual, the discourse and practices of religious moderation potentially to develop in others Islamic madhab, such as Shia. This article investigates on how the Shia community struggling over discrimination by developing the middle position in religious practices. This article offers an alternative perspective on religious moderation by referring to the religious thoughts and practices carried out by the congregation of All-Indonesian Assembly of Ahl al-Bayt Association (IJABI). This paper aims to investigate a model of religious moderation from Shia perspective. The identification for religious moderation from Shia perspective refers to the definition, characteristics, and indicators from the Indonesian Ministry of Religious Affairs, which includes three pillars, namely moderation in religious thought, method of dakwah, and religious traditions and practices. This paper argues that the congregation of IJABI practices religious moderation which consist of a teaching of prioritizing morality over fiqh, the use of the term Ahl al-Bayt, the inclusive dakwah, and the mission of the IJABI to accommodate all Muslims from different madhabs, and the commemoration of Ashura in a local culture.